Composición y estructura de un ensamble de plantas acuáticas vasculares de una represa alto andina (Santander), Colombia (2011)
ABSTRACT: The aquatic flora of the Berlin dam reservoir (Santander) Colombia, located in an area of dry páramo at an altitude of 3214 m, was studied to observe the effects that dam construction would have on it. Three samples were collected in transects that ran from the shore to the center of the reservoir during three different climate periods. A total of 28 species of aquatic plants were recorded, distributed in 17 families, most of them exhibiting an emergent life form. The family with the greatest number of species was Poaceae with ve species; however, the species with the highest relative abundance (coverage) was Myriophyllum aquaticum (halogaraceae). There were no signi cant differences in species richness during the three sampling seasons. In analyzing the spatial composition along the transects, the dynamics of this assemblage of vascular acuatic plants was observed, with a turnover of seven species in the three sampling periods. Spatial changes were most evident, with the transects in the coastal zones showing not only more changes in composition but also in species richness, while the limnetic zone retained its original composition. Conductivity was the factor that showed the greatest in uence on richness.